The degree of practice transformational leadership of public school principals in Ma'an and its relation to the level of teachers' organizational trust - Shukirat, Mohammed Falah Mohammed; al-Jazi, Raeda Abdul Karim Da'san (Journal of Educational and Psychological Sciences, 2019)
This study aimed to investigate the degree of practice transformational leadership of public school principals in Ma'an and its relation to the level of teachers' organizational trust from the teachers from their point of view. The study population consisted of all teachers in public schools in Ma'an directorate first, was selected a stratified random sample of it, consisted of (415) teachers, were used questionnaire, The degree of practice of transformational leadership of public school principals was high, and the order of dimensions ordered by means is as follows: ideal influence, the individual consideration, inspiration, and the stimulation intellectual. There are no statistically significant differences in the degree of practice transformational leadership of public school principals in Ma'an from the point of view of teachers attributed to gender. There is a strong relationship statistically significant difference between the degree of practice of transformational leadership of public school principals and the level of teachers' organizational trust.
Keywords: Degree of practice; Public school principals; Transformational Leadership; Organizational trust